Saggi di anglistica e americanistica Ricerche in corso - Ornella De Zordo (Strumenti per la didattica e la ricerca, 2009)
Saggi brings together the results of the research activity carried out in 2008 on the PhD course in English and American Studies (Department of Modern Philology, University of Florence). The seven contributions relate to the theatre, narrative, poetry, autobiographical writing and correspondence, and range from the Renaissance up to the present day, offering critical perspectives that go from the analysis of the postmodern identity to the phenomenon of rewriting, from reception theories to comparative studies, and from literary topography to computational linguistics. The heterogeneity of the material illustrates the free choice of the young academics who, in the climate of collaboration that was established, decided to address the technical and editorial aspects of the book as a team in the open access editorial workshop of the Department.